A Pragmatic Analysis of Conversational Implicature in Uglies (2024) - Rahma, Rahma Ananditha Firdaus; Satria, Robby (PROJECT (Professional Journal of English Education), 2025)
This study investigates conversational implicature in the movie Uglies (2024) through a pragmatic analysis, focusing on generalized and particularized types. The analysis is based Levinson’s (1983) theory, which distinguishes between implicatures understood from general knowledge and those requiring specific contextual information. A qualitative research design was employed, utilizing the observation method combined with non-participatory technique. Data were collected by transcribing and closely analyzing the dialogue, focusing on identifying the intended meanings beyond the literal words. The analysis method followed pragmatic identity method, which was applied to interpret the implied meanings in each identified instance. This research A total of 47 data points were identified and categorized, with 47% falling under generalized conversational implicature and 53% under particularized conversational implicature. The findings reveal that particularized implicatures are more prevalent in the movie, as the characters often engage in context-dependent dialogues to convey subtle meanings. The study highlights how conversational implicature serves as a tool for character development and thematic expression in the film. By analyzing selected data, this research provides insights into the use of language to imply meanings beyond literal expressions, contributing to a deeper understanding of conversational dynamics in movie dialogue.